Direct determination of discrete harmonic bath parameters from molecular dynamics simulations. Issue 2 (14th November 2016) - Walters, Peter L.; Allen, Thomas C.; Makri, Nancy
Abstract : We present a direct procedure for determining the parameters of a discrete harmonic bath modeling the influence of a complex condensed phase environment on the system of interest. The procedure employs an efficient discretization of the spectral density into modes that correspond to equal fractions of the reorganization energy. The new procedure uses directly the classical correlation function (available from molecular dynamics calculations) as input, avoiding numerical computation of the spectral density by means of a discrete Fourier transform. Convergence is obtained using a shorter time length of the correlation function, leading to significant computational savings. © 2016 Wiley Periodicals, Inc. Abstract : Discrete harmonic bath parameters are extracted directly from the short‐time part of time correlation functions computed via molecular dynamics methods. The figure illustrates the placement of the discrete mode frequencies in intervals of equal reorganization energy.